Antioxidant Response during the Kinetics of Anhydrobiosis in Two Eutardigrade Species - Ilaria Giovannini; Paola Antonia Corsetto; Tiziana Altiero; Gigliola Montorfano; Roberto Guidetti; Angela Maria Rizzo; Lorena Rebecchi (Life, 2022)
Anhydrobiosis, a peculiar adaptive strategy existing in nature, is a reversible capability of organisms to tolerate a severe loss of their body water when their surrounding habitat is drying out. In the anhydrobiotic state, an organism lacks all dynamic features of living beings since an ongoing metabolism is absent. The depletion of water in the anhydrobiotic state increases the ionic concentration and the production of reactive oxygen species (ROS). An imbalance between the increased production of ROS and the limited action of antioxidant defences is a source of biomolecular damage and can lead to oxidative stress. The deleterious effects of oxidative stress were demonstrated in anhydrobiotic unicellular and multicellular organisms, which counteract the effects using efficient antioxidant machinery, mainly represented by ROS scavenger enzymes. To gain insights into the dynamics of antioxidant patterns during the kinetics of the anhydrobiosis of two tardigrade species, Paramacrobiotus spatialis and Acutuncus antarcticus, we investigated the activity of enzymatic antioxidants (catalase, superoxide dismutase, glutathione peroxidase, and glutathione reductase) and the amount of non-enzymatic antioxidants (glutathione) in the course of rehydration. In P. spatialis, the activity of catalase increases during dehydration and decreases during rehydration, whereas in A. antarcticus, the activity of superoxide dismutase decreases during desiccation and increases during rehydration. Genomic varieties, different habitats and geographical regions, different diets, and diverse evolutionary lineages may have led to the specialization of antioxidant strategies in the two species.